2017
DOI: 10.1007/s12020-017-1463-6
|View full text |Cite
|
Sign up to set email alerts
|

PRMT1 promotes hyperglycemia in a FoxO1-dependent manner, affecting glucose metabolism, during hypobaric hypoxia exposure, in rat model

Abstract: PRMT1 might have a potential importance as a therapeutic target for the treatment of HH-induced maladies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Arginine methylation is involved in many biologic processes through the mechanism of posttranslation modification of histones or nonhistone proteins (16,17). For example, PRMT1 promotes hyperglycemia by methylating the transcriptional factor forkhead box O1 and thus increasing the nuclear retention and the transcriptional activity of transcriptional factor forkhead box O1 (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arginine methylation is involved in many biologic processes through the mechanism of posttranslation modification of histones or nonhistone proteins (16,17). For example, PRMT1 promotes hyperglycemia by methylating the transcriptional factor forkhead box O1 and thus increasing the nuclear retention and the transcriptional activity of transcriptional factor forkhead box O1 (17).…”
Section: Discussionmentioning
confidence: 99%
“…Arginine methylation is involved in many biologic processes through the mechanism of posttranslation modification of histones or nonhistone proteins (16,17). For example, PRMT1 promotes hyperglycemia by methylating the transcriptional factor forkhead box O1 and thus increasing the nuclear retention and the transcriptional activity of transcriptional factor forkhead box O1 (17). In the current study, we found that the expression of PRMT1 and H4R3me2a are increased in fibrotic kidneys and reduced by the treatment with PT1001B, suggesting that PRMT1 may modulate renal fibrosis through histone modificationmediated epigenetic gene regulation or even nonhistone modification-mediated transcription factor activation, which go far beyond ADMA synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, PRMTs can directly affect cell biology by modulating their protein substrates. For instance, PRMT1 promotes hyperglycemia by methylating the transcriptional factor forkhead box O1 (FOXO1) and thus increasing its nuclear retention and the transcriptional activity [112]. On the other hand, PRMTs impact on (patho)physiology via its far end metabolite product, ADMA.…”
Section: Perspectivementioning
confidence: 99%
“…Elevated levels of the phosphofructokinase gene (PFKL), 6-phosphofructo-2-kinase/fructose-2, 6-biphospatase 4 (PFKFB4) and fructose-biphosphate aldolase C (ALDOC) were seen in the RP/RP group compared with the RP/C group, which points to an activated glucose metabolism. The GO term differences in the group comparisons remained unaltered when the analysis was done without the two RP/C samples that did not cluster with the other RP F0 diet samples, with again an up-regulation of transaminase activity in the RP/C group and an up-regulation of protein arginine methyltransferase in the RP/RP group, which indeed has been described to play a role in glucose metabolism (26) .…”
Section: Functional Analysesmentioning
confidence: 91%